2021
DOI: 10.1177/10497323211012347
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Stigma Among Youth Living With HIV in Western Uganda

Abstract: We present an explanatory theory for HIV-related stigma from the perspectives of youth living with HIV/AIDS (YLWHA) in Western Uganda, on which the fight against this relentless stigma in this age group and locality can be founded. A constant comparative method was used to analyze textual data from in-depth interviews with 35 YLWHA, selected from three health facilities. A stigma process model for YLWHA was developed with the stigmatizing feelings and behaviors as the core category. Concepts delineating causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…However, baseline data do suggest our sample is fairly representative of AYAH in Kenyan and Ugandan schools, and similar to school‐age cohorts throughout Anglophone Africa. Our findings agree with previous studies that despite the optimism brought by a sense of agency, school intensifies stigma triggers, with boarding schools especially ideal for such triggers to flourish and interrupt ART adherence [35, 50, 51].…”
Section: Discussionsupporting
confidence: 92%
“…However, baseline data do suggest our sample is fairly representative of AYAH in Kenyan and Ugandan schools, and similar to school‐age cohorts throughout Anglophone Africa. Our findings agree with previous studies that despite the optimism brought by a sense of agency, school intensifies stigma triggers, with boarding schools especially ideal for such triggers to flourish and interrupt ART adherence [35, 50, 51].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in Thailand and Cambodia, 25.6% of ALWHIV reported experiencing stigma [11]. This trend is also evident in Uganda, where stigma is characterized by demeaning attitudes, gossip, and discrimination, even extending to those whose parents succumbed to HIV [17][18][19][20]. Key drivers of HIV stigma include the status disclosure, societal myths, and misconceptions about HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research in Uganda documented that adversities and challenges reported by youths living with HIV (YLWH) are not only due to the impact of HIV on their health, but are typically compounded through interactions with these surrounding systems ( Kimera et al, 2020a , b ). Although social attitudes and public discourses have evolved considerably since the emergence of the pandemic in the 1980s, they are shown to be still predominantly negative, stigmatizing and disempowering in Uganda ( Obare et al, 2011 ; Nabunya et al, 2020 ; Kimera et al, 2020b ; Kimera et al, 2021 ) and elsewhere ( Sangowawa and Owoaje, 2012 ; Mburu et al, 2014 ; Dahlui et al, 2015 ; Asamoah et al, 2017 ; Crowley et al, 2021 ; Adams et al, 2022 ). These social conditions create additional, everyday adversities for these youths, leading to self-devaluation ( Filiatreau et al, 2021 ), occupational deprivation ( Kimera et al, 2020a ) and discrimination ( Sangowawa and Owoaje, 2012 ), among other consequences that jeopardize their well-being.…”
Section: Introductionmentioning
confidence: 99%